2014
DOI: 10.1159/000362167
|View full text |Cite
|
Sign up to set email alerts
|

Specific Aspects of Consanguinity: Some Examples from the Tunisian Population

Abstract: Located at the cross-road between Europe and Africa, Tunisia is a North African country of 11 million inhabitants. Throughout its history, it has been invaded by different ethnic groups. These historical events, and consanguinity, have impacted on the spectrum and frequency of genetic diseases in Tunisia. Investigations of Tunisian families have significantly contributed to elucidation of the genetic bases of rare disorders, providing an invaluable resource of cases due to particular familial structures (large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 38 publications
0
20
0
1
Order By: Relevance
“…This high rate of consanguineous marriages in the Tunisian population has been estimated to increase sixfold the risk of an autosomal recessive disease. 31,32 Taking into account all these ascertainments, we assume that H syndrome may be underdiagnosed and we suspect that it could be even greater in Tunisia and in regions of the world where a high rate of consanguinity is noted. The reasons for underdiagnosis of H syndrome may be as follows: (i) patients with mild phenotype (subtle hyperpigmentation only for example) do not seek consultation; (ii) the lack of awareness of clinicians about H syndrome delays accurate diagnosis; and (iii) the small number of university hospitals in the internal regions of Tunisia is a major obstacle for families with limited financial resources.…”
Section: Discussionmentioning
confidence: 99%
“…This high rate of consanguineous marriages in the Tunisian population has been estimated to increase sixfold the risk of an autosomal recessive disease. 31,32 Taking into account all these ascertainments, we assume that H syndrome may be underdiagnosed and we suspect that it could be even greater in Tunisia and in regions of the world where a high rate of consanguinity is noted. The reasons for underdiagnosis of H syndrome may be as follows: (i) patients with mild phenotype (subtle hyperpigmentation only for example) do not seek consultation; (ii) the lack of awareness of clinicians about H syndrome delays accurate diagnosis; and (iii) the small number of university hospitals in the internal regions of Tunisia is a major obstacle for families with limited financial resources.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the frequency of consanguineous marriage in Arab countries including Tunisia is very high leads to an increase of the expression of autosomal recessive diseases (33)(34)(35). HGPPS seems to be another example, as all patients come from consanguineous marriage.…”
Section: Discussionmentioning
confidence: 99%
“…Combination of rare pathogen variants in DNA repair genes with high or low penetrant variants in BRCA genes among Tunisian breast cancer cases might explain the relatively young onset age and the aggressive tumor types observed in some cases described in local epidemiological reports. Our previous studies have shown a relatively high rate of consanguinity 74,75 that increases the frequency of monogenic diseases such autosomal recessive DNA repair disorders predisposing to cancer and raise the prevalence of healthy carriers 76,77 ; (Ben Rekaya unpublished data).…”
Section: Discussionmentioning
confidence: 99%